Polyethylene Terephthalate Hydrolases in Human Gut Microbiota and Their Implications for Human Health - Heqi Zhou; Songbiao Shi; Qiuhong You; Kaikai Zhang; Yuchuan Chen; Dekai Zheng; Jian Sun (Microorganisms, 2024)
Polyethylene terephthalate (PET), primarily utilized for food and beverage packaging, consistently finds its way into the human gut, thereby exerting adverse effects on human health. PET hydrolases, critical for the degradation of PET, have been predominantly sourced from environmental microbial communities. Given the fact that the human gut harbors a vast and intricate consortium of microorganisms, inquiry into the presence of potential PET hydrolases within the human gut microbiota becomes imperative. In this investigation, we meticulously screened 22,156 homologous sequences that could potentially encode PET hydrolases using the hidden Markov model (HMM) paradigm, drawing from 4984 cultivated genomes of healthy human gut bacteria. Subsequently, we methodically validated the hydrolytic efficacy of five selected candidate PET hydrolases on both PET films and powders composed of micro-plastics (MPs). Notably, our study also unveiled the influence of both diverse PET MP powders and their resultant hydrolysates on the modulation of cytokine expression in macrophages. In summary, our research underscores the ubiquitous prevalence and considerable potential of the human gut microbiota in PET hydrolysis. Furthermore, our study significantly contributes to the holistic evaluation of the potential health hazards posed by PET MPs to human well-being.